Numerical Analysis of Fluid Flow and Heat Transfer for Different Fin Designs and Arrangements of Ceramic Plate-Fin High Temperature Heat Exchanger - Part I - Yitung Chen; Vijaisri Nagarajan (Renewable Energy and Sustainable Development, 2015)
In this study numerical analysis is carried out for four different types of fins namely rectangular, triangular, inverted bolt fins and ripsaw fins and two different types of arrangements namely staggered and top and bottom arrangement. The obtained results are compared with each other and the design with best heat transfer and minimum pressure drop is selected. The working fluids used in the model are sulfur trioxide, sulfur dioxide, oxygen and water vapor. The operating pressure is 1.5 MPa and the operating temperature ranges from 973 K to 1223 K. From the results it was found that the ripsaw fin design with thickness of 0.00005 m gives a good heat transfer rate with minimum pressure drop. The inverted bolt fins also gives a good heat transfer rate but due to the fin arrangement and the flow disturbances caused by the arrangement the pressure drop is the highest compared to other fins. The pressure drop and the heat transfer obtained for the rectangular and triangular fins are similar to each other. Friction factor, Colburn j- factor and non-dimensionless numbers like Nusselt number, Schmidt number are calculated for all the models. The average Nusselt number obtained for the ripsaw fin design with thickness of 0.00005 m for the staggered and top and bottom arrangement are 3.197 and 3.023. The friction factor for the ripsaw fins for the staggered and the top and bottom arrangement are 0.522 and 0.589.